The Influence of the Police Professional Code of Ethics and Organizational Commitment on the Quality of Police Services and Its Implications for the Performance of Police Members in the Sumedang Police Environment - Paroli; Yudi Abdul Gani (International Journal of Economics (IJEC), 2023)
The essence of this research is to determine the influence of the police professional code of ethics, organizational commitment and service quality on the performance of Polri members in the Sumedang Police Station. The method used is a quantitative research method. The research results prove that the Police Professional Code of Ethics and Organizational Commitment influence the Quality of Service in the Sumedang Police Environment. The magnitude of the influence of the Police Professional Code of Ethics and Organizational Commitment on Service Quality is 85.1%. The Police Professional Code of Ethics and Organizational Commitment influence the Performance of Police Officers in the Sumedang Police Station. The magnitude of the influence of the Police Professional Code of Ethics and Organizational Commitment on the Performance of Police Members is 87.1%. The Police Professional Code of Ethics, Organizational Commitment and Service Quality influence the Performance of Police Officers in the Sumedang Police Station. The results of the regression test obtained the value Z = z + b1X1+ b2X2+Y = -7.578+0.170X1+0.348X2+ 0.358Y, meaning that a constant of -7.578 indicates that there is no increase in the value of the variables Professional Code for Police Ethics (X1), Organizational Commitment (X2) and Service Quality (Y), Performance of Police Members (Z) is -7.578. The simultaneous contribution of the Police Professional Code of Ethics (X1), Organizational Commitment (X2) and Service Quality which has a direct influence on the Performance of Police Officers (Z) is R2square = 0.886 or 88.6%, the remaining 0.114 or 11.4% is influenced by other factors that cannot be explained in this study.